Study about the winds as written in holly Quran and the way to mitigate their effect - Al-Banna, Ahmad; Abdulla, Hammed (Iraqi Journal of Science, 2024)
This research deals with the spiritual side in mitigate the effect of dust storms on human beings .It is discussing the names and types of winds as written in holly Quran.